Odpowiedzi

Najlepsza Odpowiedź!
2010-03-25T22:13:19+01:00
2x + 2x - y - x - 2y - 2x -y=x-4y=-3-(-2)=-3+2=-1
2a + 3b - 3a + b +2 + 4a + 3=3a+4b+5=3*(-4)+4*(-1)+5=-12-4+5=-11
4 4 4
2010-03-25T22:15:18+01:00
A) 2x + 2x - y - x - 2y - 2x -y dla x= -3 i y= -2

2x + 2x -y -x - 2y - 2x - y = x - 4y
-3 - (-8) = 5
b) 2a + 3b - 3a + b +2 + 4a + 3 = dla a= -4 i b= -1

2a +3b-3a+b+2+4a+3 = 3a +4b +5
-12 -4 +5 = -11
3 2 3
2010-03-25T22:15:54+01:00
A) 2x + 2x - y - x - 2y - 2x -y dla x= -3 i y= -2
2x + 2x - y - x - 2y - 2x -y=4x-3x-4y=x-4y

(-3)-4*(-2)=(-3)-(-8)=(-3)+8=5

b) 2a + 3b - 3a + b +2 + 4a + 3 dla a= -4 i b= -1
2a + 3b - 3a + b +2 + 4a + 3 =6a-3a+4b+5=3a+4c+5

3*(-4)+4*(-1)+5=-12-4+5=-16+5=-11

1 1 1